Improving Reproducibility in Hydrogen Storage Material Research. Issue 21 (31st August 2021) - Broom, Darren P.; Hirscher, Michael
Abstract: Research into new reversible hydrogen storage materials has the potential to help accelerate the transition to a hydrogen economy. The discovery of an efficient and cost‐effective method of safely storing hydrogen would revolutionise its use as a sustainable energy carrier. Accurately measuring storage capacities – particularly of novel nanomaterials – has however proved challenging, and progress is being hindered by ongoing problems with reproducibility. Various metal and complex hydrides are being investigated, together with nanoporous adsorbents such as carbons, metal‐organic frameworks and microporous organic polymers. The hydrogen storage properties of these materials are commonly determined using either the manometric (or Sieverts) technique or gravimetric methods, but both approaches are prone to significant error, if not performed with great care. Although commercial manometric and gravimetric instruments are widely available, they must be operated with an awareness of the limits of their applicability and the error sources inherent to the measurement techniques. This article therefore describes the measurement of hydrogen sorption and covers the required experimental procedures, aspects of troubleshooting and recommended reporting guidelines, with a view of helping improve reproducibility in experimental hydrogen storage material research. Abstract : Accurately characterising the hydrogen sorption properties of materials is critical to improving reproducibility in hydrogen storage material research. This review covers the main techniques used for this purpose, including important aspects of troubleshooting during the measurement process. It also proposes reporting guidelines for hydrogen sorption data, with the aim of improving reproducibility in the field of hydrogen storage material research.